Reconstructing urban boundaries: the dialectics of self and place - Gary Greif; Marcelo Cruz (Cybergeo)
Drawing upon the self-psychology of Heinz Kohut, this paper attempts to bridge the polarity between the built environment of the city experienced as a place which supports human aspiration and ideals, and the city experienced as a space which expresses and implements humanly debilitating economic and social forces. Through community functions which resist the forces of experienced space, individuals are reconstituted at the core of self experience while transforming space and reconstituting place in the process.